Word to the mother(tongue): Language access and Medicaid for Limited English Proficient migrants - Wayne Liou (IZA Journal of Development and Migration, 2018)
Limited language proficiency among migrants has been shown to limit migrants from various aspects of everyday life, from the labor market to government services. In the USA, language access laws have been enacted to help provide Limited English Proficient (LEP) individuals and households access to public benefits. The most extensive efforts in language access are in health care, with numerous states requiring Medicaid agencies to provide interpreters or translated documents. In this paper, I take advantage of heterogeneity in state-level language access laws to examine whether these efforts do indeed increase Medicaid take-up rates. I find that language access improves Medicaid take-up rates among LEP migrants without crowding out private health insurance; in fact, private health insurance coverage improves with the enactment of language access laws. There is some variation in efficacy across states, with some evidence that California and New York are the main drivers of the increased take-up rates. Lastly, I find that even though many of the language access laws primarily target Spanish speakers, the laws might not be as helpful to Spanish-speaking migrants.
Keywords: I13; I18; J15; 330; Immigrants; Language access; Government services; Medicaid